ANALISIS DETERMINAN KESEMPATAN KERJA DALAM SEKTOR INDUSTRI DI PROVINSI BANTEN - Puspita Ni Putu Rekha; Sudibia I Ketut (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2019)
The purpose of this research for analyze the affecting factors of industrial sector’s job opportunities in Banten Province such as the total industry, education rate, inflation rate, and investment. This research conducted in Banten Province and is a associative quantitative research. The method of collecting data are non-partisipan abservation and in-depth interview with relevant sources. The analysis technique used is multiple linear analysis with SPSS program for the test. The result of this research show that the education rate, inflation rate, and investment have significant and positive effect for job opportunities in industrial sector’s Banten Province, but the total of industry hasn’t positive and insignificant effect for job opportunities in industrial sector’s Banten Province. Coefficient determination (R2) amount 0,987 it mean that 98,7 percent total variance of job opportunities in industrial sector’s Banten Province are affected by total industry, education rate, inflation rate, and investment.